Multi-Substrate Terpene Synthases: Their Occurrence and Physiological Significance - Pazouki, Leila; Niinemets, Ülo (Frontiers in Plant Science, 2016)
Terpene synthases are responsible for synthesis of a large number of terpenes in plants using substrates provided by two distinct metabolic pathways, the mevalonate-dependent pathway that is located in cytosol and has been suggested to be responsible for synthesis of sesquiterpenes (C15), and 2-C-methyl-D-erythritol-4-phosphate pathway located in plastids and suggested to be responsible for the synthesis of hemi- (C5), mono- (C10) and diterpenes (C20). Recent advances in characterization of genes and enzymes responsible for substrate and end product biosynthesis as well as efforts in metabolic engineering have demonstrated existence of a number of multi-substrate terpene synthases. This review summarizes the progress in the characterization of such multi-substrate terpene synthases and suggests that the presence of multi-substrate use might have been significantly underestimated. Multi-substrate use could lead to important changes in terpene product profiles upon substrate profile changes under perturbation of metabolism in stressed plants as well as under certain developmental stages. We therefore argue that multi-substrate use can be significant under physiological conditions and can result in complicate modifications in terpene profiles.